Women and the art and science of collecting in eighteenth-century Europe - Leis, Arlene; Wells, Kacie (Histories of material culture and collecting, 1700-1950., 2021)
"Through both longer essays and shorter case studies, this book examines the relationship of European women from various countries and backgrounds to collecting, in order to explore the social practices and material and visual cultures of collecting in eighteenth-century Europe. It recovers their lives and examines their interests, their methodologies, and their collections and objects - some of which have rarely been studied before. The book also considers women's role as producers, that is creators of objects that were collected. Detailed examination of the artefacts - both visually, and in relation to their historical contexts - exposes new ways of thinking about collecting in relation to the arts and sciences in eighteenth-century Europe. The book is interdisciplinary in its makeup and brings together scholars from a wide range of fields. It will be of interest to those working in art history, material and visual culture, history of collecting, history of science, literary studies, women's studies, gender studies, and art conservation"--